Toxicity of Castor bean oil on Helicoverpa zea and Trichogramma pretiosum - Bestete, Luziani Rezende; Pratissoli, Dirceu; de Queiroz, Vagner Tebaldi; Celestino, Flávio Neves; Machado, Lorena Contarini (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the effects of castor bean oil on the tomato fruitworm, Helicoverpa zea, and on the egg parasitoid Trichogramma pretiosum. Mortality of tomato fruitworm was determined for larvae subjected to castor bean oil ingestion and contact at concentrations 0.5, 1.0, 1.5, 2.0, 2.5 e 3.0% (v v‑1). The castor bean oil action on T. pretiosum was determined by selectivity and susceptibility tests. The greatest larvae mortalities were observed in the treatment by contact with the lowest concentrations (0.5 and 1.0%), while at intermediate concentrations (1.5, 2.0, and 2.5%) there were no differences between the ways of application. At the highest tested concentration of castor bean oil (3.0%), the ingestion treatment caused a higher mortality, in comparison to the treatment by contact. The number of eggs parasitized by T. pretiosum was negatively affected by castor bean oil in the selectivity test; however, other evaluated parameters for selectivity and susceptibility were not affected. Castor bean oil reduces survival of H. zea larvae both by ingestion and contact. In addition, it does not affect the development of T. pretiosum, since sprayings are performed after releasing of the parasitoid.